The Buddhist Pancha Sheel (five precepts) and its application in governance (Triyuga Academic Journal, 2025)
The Five Precepts, also known as the Pancha Sheel, are a cornerstone of Buddhist ethics. These concepts, which have historically been attributed to individual behavior, have important ramifications for governance. The Pancha Sheel's historical, philosophical, and current significance in national governance is examined in this paper. We investigate how these principles—abstaining from killing, stealing, sexual misconduct, false speech, and intoxication—can support moral political leadership, socioeconomic advancement, and global diplomacy. Considering political complications, cultural differences, and contemporary ethical issues, the study also discusses the limitations and difficulties in putting these ideas into practice at the state level. The qualitative research design is exploited for this research.